The World Bank atlas (International Bank for Reconstruction and Development, 2004)
This edition of the World Bank Atlas provides an overview of development efforts directed toward alleviating poverty and highlights countries’ key social, economic, and environmental achievements. After an unprecedented increase during the 20th century, global population growth is decelerating. The number of people living in poverty in developing countries has declined in the past 20 years. People are living longer and enjoying healthier lives. Fewer children under five are dying, and more children are completing primary school.